Bangladesh Jobs Diagnostic - Farole, Thomas; Cho, Yoonyoung; Bossavie, Laurent; Aterido, Reyes (World Bank, Washington, DC, 2017)
This Jobs Diagnostic presents the characteristics and constraints of the labor market in Bangladesh, identifies the objectives of the jobs agenda, and proposes a policy framework to progress toward them. This multisectoral diagnostic assesses the relationships between supply- and demand-side factors that interact to determine job creation, quality, and inclusion outcomes. Understanding the factors that influence jobs outcomes requires a holistic approach capturing issues such as access to markets, inputs, capital, technology, skills, and matching of supply and demand. Standard labor analysis tends to miss crucial aspects of the demand side of job creation, while growth diagnostics have no direct link to jobs. The Jobs Diagnostic thus intends to provide the comprehensive evidence base to support the development of a national jobs strategy that focuses on policies to foster an environment for more, better, inclusive jobs in Bangladesh.